Temperature dependent viscosity of mixtures of ionic liquids at different compositions - Khupse, Nageshwar D.; Kurolikar, Shabana R.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
This work presents experimental investigations of viscosities of the mixtures of ionic liquids, viz., [bmim][BF(4)] + [bmim][PF(6)] and [hmim][BF(4)] + [hmim][PF(6)] at different temperatures. The temperature dependence of viscosities of these mixtures has been analysed in the light of Vogel-Fulcher-Tammann (VFT) equation with excellent accuracy. The viscosities of the mixtures have been analysed using a simple mixing rule.
Keywords: ionic liquids; viscosity

Temperature effect on the molecular interactions between ammonium ionic liquids and N,N-dimethylformamide - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Journal of Physical Chemistry B, 2010)
In view of the wide scope of molecular interactions between the highly polar compound of N,N-dimethylformamide (DMF) and ammonium ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (u) over the whole composition range at temperatures ranging from 25 to 50 degrees C under atmospheric pressure. To gain some insight into the several aggregations of molecular interactions present in these mixed solvents, we predicted the excess molar volume (V(E)) and the deviations in isentropic compressibilities (Delta K(s)) as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included the hydroxide series of ammonium ILs of tetramethylammonium hydroxide [(CH(3))(4)N][OH] (TMAH), tetraethylammonium hydroxide [(C(2)H(5))(4)N][OH] (TEAH), and tetrapropylammonium hydroxide [(C(2)H(7))(4)N][OH] (TPAH). The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion-dipole and ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Thermodynamic and molecular origin of interfacial rate enhancements and endo-selectivities of a Diels-Alder reaction - Beniwal, Vijay; Kumar, Anil (Physical Chemistry Chemical Physics, 2017)
Organic reactions in general display large rate accelerations when performed under interfacial conditions, such as on water or at ionic liquid interfaces. However, a clear picture of the physicochemical factors responsible for this large rate enhancements is not available. To gain an understanding of the thermodynamic and molecular origin of these large rate enhancements, we performed a Diels-Alder reaction between cyclopentadiene and methyl acrylate at ionic liquid/n-hexane interfaces. This study describes, for the first time, a methodology for the calculation of the activation parameters of an interfacial reaction. It has been seen that the energy of activation for an interfacial reaction is much smaller than that of the corresponding homogeneous reaction, resulting into the large rate acceleration for the interfacial reaction. Furthermore, the study describes the effects of the alkyl chain length of ionic liquid cations, the extent of heterogeneity, and the polarity of ionic liquids on the rate constants and stereoselectivity of the reaction.

Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage